Ultraviolet-C and atmospheric pressure plasma jet inactivation of Pseudomonas aeruginosa cocktail on different stainless steel surfaces - Ugay, Maria Chelsea Clarisse F.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines, 2015)
The purpose of this research was to study ultraviolet-C and atmospheric pressure plasma jet as methods for inactivation of Pseudomonas aeruginosa on different stainless steel surfaces. The types of stainless steel used in the study were types 316 and 304, each having mirror (MR), hairline (HL) and 2B surface finishes. P. aeruginosa cocktail in mid-stationary phase (20 h) was prepared and allowed to adhere on the surface of stainless steel samples for 4 h, after which the cells were subjected to UV-C and atmospheric pressure plasma jet treatments. Survival curves generated from UV-C inactivation revealed a biphasic inactivation behavior characterized by an initial faster log linear inactivation followed by a slower inactivation tail. Calculated UV-C D1-values ranged from 2.06 s (304 MR) to 5.60 s (316 2B). The maximum log reductions prior to the inactivation tail of UV-C treated P. aeruginosa on different stainless steel surfaces ranged from 3.48 log CFU/in2 (304 MR) to 4.71 log CFU/in2 (304 2B). Conversely, atmospheric pressure plasma inactivation study produced logarithmic linear death curves, and the D-values determined ranged from 1.95 s (304 HL) to 3.27 s (304 2B). The efficacies of both disinfection methods were observed not to be influenced by metal type and surface finish. These results showed that UV-C treatment may be used in combination with relatively milder chemical disinfection treatment, while atmospheric jet plasma may be used solely for food contact surface disinfection.
Thesis Classification: P (For Publication)
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Pseudomonas aeruginosa -- Philippines; Plasma jets